Kajian Indikator Proses Pembelajaran Praktek Pengelasan Di SMK - Muhamad Dwi Ariyanto; Yuyun Estriyanto; Budi Budi Harjanto (Nozel : Jurnal Pendididikan Teknik Mesin, 2022)
Abstract The objectives of the study are: (1) to find the indicators of welding teaching and learning process which is appropriate to the characteristics of welding ability, (2) to know the ideal magnitude of every indicator in qualified SMAW welding teaching and learning process.The approach of the survey which is used in this research is the combination of qualitative and quantitative with sequential exploratory model of descriptive method. The first step applied is qualitative method and the second step is quantitative method. The technique of collecting data were interview and questionnaire. The respondents of the study was chosen by certain consideration.The results of the study are: (1) the indicators of welding process in teaching and learning practice are teaching and learning model, students’ character, physical condition, psychological condition, duration of the practice session, and teaching and learning practice frequency. (2) Satisfied result was found when the teaching and learning held once in a week, one meeting is 8 teaching hours. (3) The material delivery within 16 meetings is enough to be understood by students. (4) The mastering position of welding is ideally for 1G or 1F needs 3 meetings, 2G or 2F needs 5 meetings, and 3G or 3F needs 8 meetings. (5) 16 meetings for welding teaching and learning practice is not enough to master the SMAW welding competency.